2018
DOI: 10.2217/cnc-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Sex & gender considerations in concussion research

Abstract: The study of concussion, a common form of mild traumatic brain injury, has received increased notice over the last decade. Recently, more researchers have been addressing the historic paucity of attention over sex and gender influences on recovery outcomes after concussion. This development has led to exciting progress in our understanding of concussion incidence and outcomes. In this review, we will report on new findings from varying studies on sex differences in the epidemiology of concussion and clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 51 publications
3
65
0
1
Order By: Relevance
“…ere are various reasons as to why females experience more symptoms and greater severity of symptoms after suffering a concussion compared with their male counterparts. Biomechanical differences seem to contribute to symptom status due to disparities in the neck musculature and head/neck stability in females making them more susceptible to injury [6]. Males also have greater cortical neuronal densities, while females have a greater number of neuropils [11].…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations
“…ere are various reasons as to why females experience more symptoms and greater severity of symptoms after suffering a concussion compared with their male counterparts. Biomechanical differences seem to contribute to symptom status due to disparities in the neck musculature and head/neck stability in females making them more susceptible to injury [6]. Males also have greater cortical neuronal densities, while females have a greater number of neuropils [11].…”
Section: Agementioning
confidence: 99%
“…ere is also evidence that females report more symptoms and a greater severity of symptoms than males after suffering a concussion because it is more socially acceptable for women to admit vulnerability than it is for men [6]. However, Broshek et al [11] reported that females do in fact experience more severe postconcussion symptoms than males and that poorer outcomes are not simply due to cultural-based sex differences in symptom reporting.…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…We have also reported the effects of neurofeedback on these changes during the acute recovery period (Ims & Kerasidis, 2018). Studies have identified gender differences in the incidence, severity, and recovery time from sport concussion injury, all increased in females (Cantu, 2010;Hamson-Utley et al, 2013;Miyashita, Diakogeorgiou, & VanderVegt, 2016;Mollayeva, El-Khechen-Richandi, & Colantonio, 2018;Tanveer, Zecavati, Delasobera, & Oyegbile, 2017). The objective of this investigation is to explore gender differences in volumetric qEEG analysis after sport concussion injury in high school athletes.…”
Section: Introductionmentioning
confidence: 99%